Parallel and distributed programming using C++ - Hughes, Cameron; Hughes, Tracey ([S.l.] : Addison-Wesley Professional, 2003)
Today, the C++ language remains one of the most important languages used by professional software developers. Many corporations and government agencies have large investments in applications that are developed using the C++ language. Those corporations and government agencies are now Web-enabling their applications. Applications that were originally developed as simple client/server now requires Internet/Intranet face-lifts. This book helps software developers and programmers who need to add the techniques of parallel and distributed programming to existing applications. Parallel programming uses multiple computers, or computers with multiple internal processors, to solve a problem at a greater computational speed than using a single computer. It also offers the opportunity to tackle larger problems; that is, problems with more computational steps or more memory requirements.